Evaluation of maxillary sinus floor augmentation with the crestal approach and beta-tricalcium phosphate: a cone-beam computed tomography 3- to 9-year follow-up - Oba, Yoko; Tachikawa, Noriko; Munakata, Motohiro; Okada, Tsuneji; Kasugai, Shohei (International journal of implant dentistry, 2020)
Background We performed maxillary sinus floor augmentation using the crestal approach and beta-tricalcium phosphate (β-TCP) and a long-term evaluation using cone-beam computed tomography (CBCT). Methods Twenty-three patients (30 implants) underwent sinus floor augmentation using the osteotome technique. Subjects underwent CBCT imaging before surgery, immediately after surgery, and at follow-up (≥ 3 years after surgery). We measured the changes in height of the augmented sinus floor (SL), the augmented bone above apex of the implant (BH), and the implant length that projected into the sinus (IL). Results The mean SL decreased from 6.54 ± 1.51 (immediately after surgery) to 3.11 ± 1.35 mm (follow-up). The mean BH decreased from 3.17 ± 0.97 to − 0.25 ± 1.19 mm; the maxillary sinus floor in many implants was near the apex at follow-up. The SL at follow-up showed a strong correlation with the IL ( p = 0.0057). Conclusions Osteotome sinus floor elevation with beta-tricalcium phosphate was clinically effective. Cone-beam computed tomography analysis revealed that ≥ 3 years after surgery, the maxillary sinus floor was near the apex of the implant.